Some Determinants of Green Consumption Behavior: A Study on Green Consumers - AYDIN, Hatice (Journal of Environmental Management and Tourism; Vol 7 No 4 (2016): JEMT Volume VII Issue 4(16) winter 2016, 2017)
The usage of environmentally friendly products has been growing in recent years, and many factors affect such usage. The present study explains the influence of some important determinants on green consumption behavior. These factors namely, consumer effectiveness, environmental knowledge, and environmental concern were determined as input variables whereas; green consumption behavior was an output variable. A survey was conducted to green consumers in Istanbul. The results indicated that perceived consumer effectiveness, environmental concern, and environmental knowledge had a significant positive effect on green consumption behavior.